Spatiality and Human Development in the Western Cape of South Africa - Dube, Primrose Sikhanyiso (Department of Social Development, 2023)
This study explored how spatiality influenced human development in the Western Cape and specifically Cape Town, in the post-apartheid era. It argued for the incorporation of the spatiality dimension into the traditional Human Development Index (HDI), while focussing on pertinent strategies to transform the inherited colonial and apartheid spatial patterns to enhance human development. Significantly, the research arrived at a model that incorporates the spatiality dimension into the standard HDI in order to measure human development by focussing on the concept of spatial justice. The research study adopted a mixed methods design, that is based on integrating qualitative and quantitative research methods, however, much emphasis was on the qualitative research method. Data collection was done through the following: 62 in-depth interviews for the qualitative part of the research study, and a survey of 62 structured interviews with closed-ended questions were undertaken for the quantitative part of the research, and with different secondary sources. An embedded design was utilised, whereby the quantitative method was embedded within a primarily qualitative method, in order to allow information to be sought from a different level. The second data set (quantitative data) was collected after the first data collection (qualitative data), and this technique was viable for this research. Tesch's approach was used to analyse the qualitative data, and the Statistical Product and Service Solutions was used to analyse the quantitative data. Some of the substantial findings of the study are the following: spatiality has a positive or negative impact on human development depending on people's geographic location and the resources available to them within such spaces; those who are confined to urban poor vicinities face various challenges that affect their human development outcome, whereas, the affluent enjoy the benefits of residing in healthy and safe environments, thus, enhancing their human development opportunities; there has been minuscule spatial transformation in the Western Cape since the end of apartheid; hence, more resources and spatial justice are needed, particularly in poor communities, for the province to have better human development outcomes; and lastly, spatiality is a potential dimension of human development that needs to be incorporated into the traditional HDI because where one resides will most likely determine his or her human development outcomes. The conclusions of the study, among others, posit that better human development for everyone is possible when there is spatial justice. Importantly, an HDI that includes the spatiality dimension will be beneficial to South Africa and especially the Western Cape province, and other countries, as it will sharpen the development of public policies, social policies, and spatial planning. Hence, more involvement from government and civil society development actors is needed in the deprived areas of the Western Cape, especially the following key role players: national, provincial and particularly the local government spheres; community members, community-based organisations (CBOs), non-governmental organisations (NGOs), international organisations, faith-based organisations and the private sector. Recommendations are offered by the study to these key role players with emphasis on the government to double its efforts to foster spatial justice.